Efeito da irrigação na produção e estabelecimento de mudas de eucalipto - Bernardino, Lynniker Trés (2015)
Brazil currently has about 7.6 million hectares of planted forests thus playing a key role in socio-economic scenario of the country. Establish relationships between water consumption by eucalyptus cultivation and water availability in the growth substrate of the plants or soil of post-planting, helps to predict the productive potential of forest plantations, given that the different water availability conditions influence their productivity at the end of the cycle. Research has sought new technologies to establish more productive forests, among these researches is the hidroretentor gel that has function to increase the availability of water for the plant, in the most critical phase of the establishment of the changes in the field. Within this context, the testing in order to evaluate the effect of increasing water supplies on the obtained yields can generate important information for the management of eucalyptus cultivation. As a result of the proposed aspects, the present study had the following objectives: to study the relationship between eucalyptus cultivation and the water supply in growing and hardening in the production of E. grandis vs. E. urophylla - 6064 in the nursery and evaluate the influence of using a gel and water solution applied in pre-irrigation before planting, and its influence in the establishment and development of clonal seedlings of hybrid Eucalyptus grandis x E. urophylla - 03 in the first six months after transplant. Thus, we performed two experiments. The first was held in São Mateus - ES, which was carried out tests with six different irrigation levels, 4 of these blades based on reference evapotranspiration (50, 100, 200, 300% of ETo) and 2 treatments based on the voltage Water on the substrate (3 and 6 kPa). In this study it was concluded that the greatest water depths from treatments of 200 and 300% of ETo, provided the further development of seedlings, enabling reached the same standards set for their shipment and subsequent planting. The second part of this work was conducted in an area of commercial planting in Chapadinha-MA. The study was divided into 7 treatment (transplanted without the use of the gel; conventional transplantation, increasing doses 1.0g 5L1 , 2.0g 5L-1 , 3.0g 5L-1 , 4.0g 5L-1 and 5.0g 5L-1 gel solution per liter of water in the pre-irrigation) and 3 replicates. It was found that higher dosage gel + solution in pre-irrigation water gave a significant increase in plant height, stem diameter. However, for this period, it was observed that higher doses gel + solution Water provide a lowest root development.